Looking at Queer/Cuir in Ibero-American Translation - Villanueva-Jordán, Iván (2023)
Based on a review of the figure of James S. Holmes as a pioneer of contemporary translation studies, this introductory article identifies some critical aspects of reflection on queerness in translated cultural artifacts. To do so, the article is divided into three sections drawing from theoretician Alberto Mira’s concept of “unsubmissive look” (mirada insumisa) to recognize queer trajectories in translation studies from its disciplinary inception to the emergence of gender approaches to the research articles gathered in this special issue. The second section briefly reviews how “queer” is understood and has been translated in Spanish until the current coinage cuir. The third section proposes a conceptual organization of how gender has permeated translation studies by emerging relational categories such as “translation and gender,” “translation and queer,” and “translation and trans.” The article concludes with a brief presentation of the twelve articles collected in this issue.